1998
DOI: 10.1007/s002130050778
|View full text |Cite
|
Sign up to set email alerts
|

The nitric oxide synthesis inhibitor nitro- L -arginine ( L -NNA) attenuates nicotine abstinence syndrome in the rat

Abstract: Nitric oxide synthesis contributes to opiate tolerance and dependence. Nicotine dependence and abstinence syndrome in the rat appear to involve opiate mechanisms. Therefore, it was postulated that nitric oxide synthase (NOS) activity might be essential for the expression of nicotine abstinence syndrome. Twenty-one rats were rendered dependent by SC infusion of 9 mg/kg per day nicotine tartrate via Alzet osmotic minipump. Rats were pretreated SC with vehicle alone, or with 18 or 30 mg/kg of the NOS inhibitor L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…In contrast, genetic deletion of the β4 subunit eliminated somatically expressed nicotine withdrawal behaviors in the mouse (Salas et al 2004). Centrally administered hexamethonium, a noncompetitive nicotinic receptor antagonist with relative specificity for α3β4 receptors, precipitated somatically expressed nicotine withdrawal signs with enormous potency (Malin et al 1997), particularly as compared with DHβE (Malin et al 1998b). One speculative possibility is that α4β2 receptors, with their close connection to reinforcement mechanisms, might be responsible for withdrawal-induced changes in those mechanisms, while α3β4 receptors might be involved in the heightened irritability leading to somatically expressed nicotine withdrawal signs.…”
Section: Cholinergic Mechanismsmentioning
confidence: 81%
See 2 more Smart Citations
“…In contrast, genetic deletion of the β4 subunit eliminated somatically expressed nicotine withdrawal behaviors in the mouse (Salas et al 2004). Centrally administered hexamethonium, a noncompetitive nicotinic receptor antagonist with relative specificity for α3β4 receptors, precipitated somatically expressed nicotine withdrawal signs with enormous potency (Malin et al 1997), particularly as compared with DHβE (Malin et al 1998b). One speculative possibility is that α4β2 receptors, with their close connection to reinforcement mechanisms, might be responsible for withdrawal-induced changes in those mechanisms, while α3β4 receptors might be involved in the heightened irritability leading to somatically expressed nicotine withdrawal signs.…”
Section: Cholinergic Mechanismsmentioning
confidence: 81%
“…Chronic nicotine exposure increases nitric oxide metabolites in multiple brain regions (Pogun et al 2000), and there is persistently increased hypothalamic nitric oxide response to food deprivation following nicotine withdrawal (Mannucci et al 2005). Several inhibitors of nitric oxide synthase prevent mecamylamine-precipitated nicotine withdrawal syndrome and reverse spontaneous withdrawal syndrome, as indicated by somatically expressed behaviors (Adams and Cicero 1998;Malin et al 1998b). Finally, ion channel events are also likely to participate in the expression of nicotine withdrawal syndrome.…”
Section: Signal Transduction Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is considered to play an important role in the neurobiology of addiction (Uzbay and Oglesby 2001). For instance, Malin et al (1998) reported that Nnitro-L-arginine (L-NNA), a NOS inhibitory agent, suppressed the severity of all signs of nicotine abstinence; and, this suppressive effect of L-NNA was reversed by Larginine, a NO precursor, suggesting an effect specific to NOS. Also, previous studies indicated that preventing NO formation by several NOS inhibitors could reverse both the acute locomotor activity enhancing effect of psychostimulant agents (Przegalinski and Filip 1997;Çelik et al 1999) and development of locomotor sensitization (Pudiak and Bozarth 1993;Ohno and Watanabe 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Some studies reported that the high concentration of NO in cigarette smoke interferes with the action of enzyme NOS or lowers the level of NOS (5). In rats, NOS inhibitors can alleviate symptoms of the nicotine abstinence syndrome, and co-administration of L-arginine is likely to diminish the attenuating effect of the the NOS inhibitor (6). NOS has three distinct isoforms; neuronal (nNOS/NOS1), inducible (iNOS/NOS2) and endothelial (eNOS/NOS3) (7).…”
Section: Introductionmentioning
confidence: 99%